Global and local actions for sustainable development: an analysis and attempt at synthesis - Frankowicz, Marek (Uniwersytet Rzeszowski: Południowo-Wschodni Oddział Polskiego Towarzystwa Inżynierii Ekologicznej z siedzibą w Rzeszowie, 2025)
Sustainable development constitutes one of the key paradigms shaping contemporary public policies, development strategies, and social actions. This article presents an overview and a synthetic analysis of actions undertaken in support of sustainable development at three levels: global (world and Europe), national (Poland), and local (the Małopolska region). The analysis encompasses normative frameworks and top-down policies as well as bottom-up initiatives, the role of education, higher education institutions, and regional partnerships. The aim of the article is not to provide a detailed evaluation of the effectiveness of individual instruments, but rather to present an overview of current activities, identify key actors and mechanisms, and highlight the importance of coherent, systemic, and multi-level approaches to sustainable development.

Zrównoważony rozwój stanowi jeden z kluczowych paradygmatów współczesnych polityk publicznych, strategii rozwojowych oraz działań społecznych. Artykuł przedstawia przegląd i syntetyczną analizę działań podejmowanych na rzecz zrównoważonego rozwoju na trzech poziomach: globalnym (świat i Europa), krajowym (Polska) oraz lokalnym (region Małopolski). Analiza obejmuje zarówno ramy normatywne i polityki odgórne, jak i inicjatywy oddolne, rolę edukacji, szkolnictwa wyższego oraz partnerstw regionalnych. Celem artykułu nie jest szczegółowa ewaluacja skuteczności poszczególnych instrumentów, lecz przedstawienie panoramy aktualnych działań, identyfikacja kluczowych aktorów i mechanizmów oraz wskazanie znaczenia spójnych, systemowych i wielopoziomowych podejść do zrównoważonego rozwoju.
Działania globalne i lokalne na rzecz zrównoważonego rozwoju: analiza i próba syntezy
Keywords: sustainable development; Agenda 2030; systems approach; education; public policies; zrównoważony rozwój; podejście systemowe; edukacja; polityki publiczne